2021
DOI: 10.3389/fendo.2021.664183
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factor Status in Hospitalized Patients With Type 2 Diabetes in China

Abstract: BackgroundControlling blood glucose, blood pressure, and blood lipid is of great importance for patients with type 2 diabetes, not only for cardiovascular disease, but also for other complications. Previous studies mainly focused on the control rate of outpatients, and the results were suboptimal, but few studies aimed at the inpatients.MethodThe present study involved 3,245 hospitalized patients with type 2 diabetes from 2013 to 2017 in the Department of Endocrinology and Metabolism of Tianjin Medical Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In a recent metaanalysis, the achievement rates for the control of CVD risk factors—glycemic control, blood pressure, LDL-C, HDL-C, and TG—were 42.8%, 29%, 49.2%, 58.2%, and 61.9% respectively [ 16 ]. During 2013 and 2017, control rates of HbA 1C , LDL-C, and blood pressure had increased among hospitalized T2DM patients in Tianjin, China [ 17 ]. A crosssectional study conducted in a tertiary care teaching hospital in Wardha District, India, demonstrated that only one-fourths of T2DM patients have the optimal control of one or more risk factors for CVD, including physical inactivity, tobacco use, hypertension, obesity, dyslipidemia, and dietary risk factors [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent metaanalysis, the achievement rates for the control of CVD risk factors—glycemic control, blood pressure, LDL-C, HDL-C, and TG—were 42.8%, 29%, 49.2%, 58.2%, and 61.9% respectively [ 16 ]. During 2013 and 2017, control rates of HbA 1C , LDL-C, and blood pressure had increased among hospitalized T2DM patients in Tianjin, China [ 17 ]. A crosssectional study conducted in a tertiary care teaching hospital in Wardha District, India, demonstrated that only one-fourths of T2DM patients have the optimal control of one or more risk factors for CVD, including physical inactivity, tobacco use, hypertension, obesity, dyslipidemia, and dietary risk factors [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis, which assessed the achievements of targets according to different guidelines in different countries, reported that the achievements rates were 42.8% for glycemic control, 29% for blood pressure, 49.2% for LDL cholesterol ( 30 ). For inpatients, the percentages of patients who met the Chinese Diabetes Society goals—HbA1c <7%, blood pressure <130/80 mmHg, normal lipids, and all three goals—were 30.5, 16.2, 8.0, and 0.9% in 2017 ( 31 ), respectively. But there are few studies about the gaps in treatment medication between real-world and guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…According to the latest data from the International Diabetes Federation (IDF), approximately 140.9 million diabetic subjects were diagnosed in China in 2021, and this number is predicted to increase to 174.4 million by 2040 [2]. A large body of evidence has shown that diabetes may lead to various potentially life threatening micro-vascular and macro-vascular complications [3][4][5].…”
Section: Introductionmentioning
confidence: 99%